2017
DOI: 10.1063/1.4995567
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Effect of density on the physical aging of pressure-densified polymethylmethacrylate

Abstract: The rate of physical aging of glassy polymethylmethacrylate (PMMA), followed from the change in the secondary relaxation with aging, is found to be independent of the density, the latter controlled by the pressure during glass formation. Thus, the aging behavior of the secondary relaxation is the same whether the glass is more compacted or less dense than the corresponding equilibrium liquid. This equivalence in aging of glasses formed under different pressures indicates that local packing is the dominant vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…5,[10][11][12] A recent paper reported that the change in the JG b-relaxation time and dielectric strength during physical aging of two PMMA glasses formed at 188 MPa and at 0.1 MPa are the same. 13 Thus, the change of the secondary relaxation with aging is found to be independent of the density, since the glass formed at high pressure of 188 MPa is denser than that formed at 0.1 MPa. To rationalize this observation, the authors of ref.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…5,[10][11][12] A recent paper reported that the change in the JG b-relaxation time and dielectric strength during physical aging of two PMMA glasses formed at 188 MPa and at 0.1 MPa are the same. 13 Thus, the change of the secondary relaxation with aging is found to be independent of the density, since the glass formed at high pressure of 188 MPa is denser than that formed at 0.1 MPa. To rationalize this observation, the authors of ref.…”
Section: Introductionmentioning
confidence: 91%
“…To rationalize this observation, the authors of ref. 13 suggested that the average density does not govern the dynamics of the glass, but rather the local structure and barriers for thermal fluctuations of density are the main control parameters. All these complicated and uneven observed changes of the secondary relaxation on aging make them inappropriate to distinguish secondary relaxation having connection to the a-relaxation or not.…”
Section: Introductionmentioning
confidence: 99%
“…42 After a comprehensive discussion it was concluded that in these cases the average density does not govern the properties of the glass, but rather the local structure and barriers for thermal fluctuations of density are the main control parameters. 38 We suggest that elastically altered states of glasses would show difference in the strength and dynamics of the JG relaxation. But no such relaxation has been known to occur in sc-C60 or C60-OG.…”
Section: B Thermal Conductivity Features On Cooling and Kinetic Freementioning
confidence: 83%
“…Both features are expected on the phenomenological basis of glass formation. 68 Also, recent dilatometric studies by Casalini and Roland 38 have found that the sub-Tg feature has moved so close to Tg that it is observed as a low-temperature broadening of the Tg. It is possible that our findings indicate a shift so large that the sub-Tog feature became undiscernible.…”
Section: B Thermal Conductivity Features On Cooling and Kinetic Freementioning
confidence: 98%
See 1 more Smart Citation